Experiences and observations from a care point for displaced Ukrainians: a community case study in Antwerp, Belgium - Morreel, Stefan; Verhoeven, Veronique; Bastiaens, Hilde; Monten, Katrien; van Olmen, Josefien (Frontiers in Public Health, 2024)
Background: 7307 Ukrainians refugees moved to Antwerp, Belgium during the study period (01/04/2022-31/12/2022). The city's administration set up three care centers where these people were introduced to the Belgian primary care system, a medical file was created, and acute/preventive/chronic care was delivered. This community case study analyses the organization and contents of care and reflects upon its meaning for the mainstream health care system. Methods: This is an observational study using routine electronic medical record data to measure uptake of care. For a sample of 200 subjects, a retrospective chart review was conducted.Participants: All refugees with a medical file at one of the three participating care centers.Main Outcomes: For the observational study, 2261 patients were reached (30% of the potential users) and 6450 contacts were studied. The nurses (including midwives) did 4929/6450 (76%) of all consultations, the GPs 1521/6450 (24%). Out of the nurse consultations, 955 (19%) were followed by another nurse consultation and 866 (18%) by a GP consultation. In the structured case reviews most contacts concerned acute problems (609/1074, 57%). The most prevalent reasons for encounter and diagnoses concerned typical primary care issues. The nurses were able to manage half of the cases independently (327, 55%), referred to the GP in 37% ( 217), and consulted a GP (live, by telephone or a dedicated app) for 8% (48). GPs mostly prescribed drugs, referred to a medical specialist and advised over-the-counter drugs while nurses more often advised over-the-counter drugs (mostly paracetamol, nose sprays and anti-inflammatory drugs), gave non-medical advice or ordered lab tests.The medical care points delivered mostly typical acute primary care in this first phase, with a key role for nurses. The care points did not sufficiently take up chronic diseases and mental health problems. These results will inform policy makers on the use of primary care centers for newly arriving patients in times of a large influx. A nurse first model seems feasible and efficient, but evaluation of safety and quality of care are needed. Once the acute phase of this crises fades away, questions about the comprehensiveness, continuity, and integration of care for migrants remain relevant.